Whatsapp Group Use for Maintaining Family Communication in Gebang Raya: Penggunaan Grup WhatsApp untuk Mempertahankan Komunikasi Keluarga di Gebang Raya - Sabilla, Talitha Rizda; Rochmaniah, Ainur (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Family communication is a fundamental component in maintaining harmonious relationships among family members. Specific Background: In the digital era, instant messaging platforms such as WhatsApp have become integral tools for facilitating daily interactions despite geographical separation. Knowledge Gap: While prior studies have explored digital communication, there is limited qualitative insight into how families in specific local contexts utilize WhatsApp to sustain relationships and balance virtual with direct interactions. Aims: This study investigates the patterns, benefits, and challenges of using WhatsApp group features for family communication in the Gebang Raya area, Sidoarjo District. Results: Data from in-depth interviews with five respondents of varied backgrounds reveal that WhatsApp enables efficient coordination, real-time sharing of life moments, and emotional support despite distance. However, recurring technical issues and privacy concerns pose limitations. Novelty: The findings highlight the conscious strategies adopted by families to maintain offline quality time, ensuring that digital convenience does not erode interpersonal bonds. Implications: These insights can inform the design of community-based digital literacy programs that promote balanced and secure technology use in family contexts.Highlights: WhatsApp fosters family closeness despite physical separation. Technical and privacy issues remain ongoing challenges. Families balance online interaction with offline quality time. Keywords: Family Communication, WhatsApp, Digital Era, Social Media, Sidoarjo